Student’s Perception on Online Instructional Media Effectiveness in Automotive Field - Tafakur Tafakur; Moch Solikin; Ayu Sandra Dewi (VANOS Journal of Mechanical Engineering Education, 2021)
Instructional media is an important component in online learning. This study aims to: 1) find out what types of learning media that motivate students to learn; 2) knowing the benefits of various types of learning media used by students on online learning. This study used ex post facto method. The questionnaire was used to gain the data from bachelor student. The instrument explores information about various forms of online learning media, namely text, audio, graphic, animation, and video. The terms of the benefits of media including able to stimulate students' curiosity, motivate student, make easier for students understanding, encourage students learning happily, and giving student’s flexibility in choosing learning resources. The results showed that: The better online learning media for motivating student were animation and video with a very high category of motivation achievement. While other types of learning media are in the high category. Judging from the benefits of various types of media, video and animation media are the most useful for students in online learning. The media got very high category on stimulating students' curiosity, motivating student`s learning, making it easier for students to understand, encouraging students learning happily, as well as giving students flexibility in choosing learning resources. Meanwhile, other types of learning media are in the high category. Even on text media, getting a low category on encouraging students learning happily. Therefore, teachers not only use PowerPoint media, but also need to consider other types of learning media for teaching students in online learning.